Pengaruh Model Beneish M-Score terhadap Kecurangan Laporan Keuangan pada Perusahaan Property dan Real Estate yang Terdaftar di Issi Periode 2021-2023 - Nurhaliza Nurhaliza (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
The property and real estate industry in Indonesia plays a strategic role in supporting national economic growth and providing employment opportunities. However, the rapid development of this sector also increases the risk of financial reporting fraud, which can harm investors and stakeholders. This study aims to analyze the effect of the Beneish M-Score model on financial statement fraud in property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2021–2023. This study uses a quantitative approach with descriptive methods and purposive sampling techniques to determine 12 companies as samples. Secondary data were obtained from company annual reports and analyzed using simple linear regression with the help of SPSS version 30. The results show that partially, the DSRI, GMI, and SGI variables have a significant effect on financial statement fraud. Meanwhile, AQI, DEPI, SGAI, LVGI, and TATA did not show a significant effect. These findings provide important insights for investors and regulators in identifying potential fraud through certain financial indicators.